The role of bisphenol A in the carcinogenesis process - Chludzińska, Sylwia; Modzelewska, Patrycja; Koda, Mariusz; Lewko, Jolanta; Reszeć, Joanna (Medical Studies/Studia Medyczne, 2018)
Bisphenol A (BPA), one of the most common endocrine disrupting chemicals, is a carbon-based synthetic compound used in the production of water bottles, cans, food packaging, dental materials, medical equipment, thermal paper, toys and articles for children. Bisphenol A has been associated with serious health effects in humans. It elicits several disorders and plays a role in the pathogenesis of several tumors such as breast, ovarian, prostate and colorectal cancer. The aim of the research is to review the latest literature assessing participation of BPA in the process of neoplasia. There is not much research on this subject and the role of BPA in the carcinogenesis is still not understood. The present review summarizes the current knowledge of the role of BPA in carcinogenesis.